Excess costs from functional somatic syndromes in Germany: an analysis using entropy balancing - Grupp, Helen; Kaufmann, Claudia; Wild, Beate; Szecsenyi, Joachim; Herzog, Wolfgang; Schellberg, Dieter; Schäfert, Rainer (Journal of psychosomatic research, 2017)
Aim: The aim of this study was to calculate disorder-specific excess costs in patients with functional somatic syndromes (FSS). Methods: We compared 6-month direct and indirect costs in a patient group with FSS (n = 273) to a control group of the general adult population in Germany without FSS (n = 2914). Data on the patient group were collected between 2007 and 2009 in a randomized controlled trial (speciAL). Data on the control group were obtained from a telephone survey, representative for the general German population, conducted in 2014. Covariate balance between the patient group and the control group was achieved using entropy balancing. Excess costs were calculated by estimating generalized linear models and two-part models for direct costs and indirect costs. Further, we estimated excess costs according to the level of somatic symptom severity (SSS). Results: FSS patients differed significantly from the control group regarding 6-month costs of outpatient physicians (+€280) and other outpatient providers (+€74). According to SSS, significantly higher outpatient physician costs were found for mild (+€151), moderate (+€306) and severe (+€376) SSS. We also found significantly higher costs of other outpatient providers in patients with mild, moderate and severe SSS. Regarding costs of rehabilitation and hospital treatments, FSS patients did not differ significantly from the control group for any level of SSS. Indirect costs were significantly higher in patients with severe SSS (+€760). Conclusion: FSS were of major importance in the outpatient sector. Further, we found significantly higher indirect costs in patients with severe SSS.